Maximum BCE synthesis of domino-tiled planar arrays for far-field wireless power transmission. Issue 17 (21st November 2020) - Anselmi, N.; Polo, A.; Hannan, M. A.; Salucci, M.; Rocca, P.
Abstract : The design of transmitting antenna arrays with a modular aperiodic architecture for far-field wireless power transmission (WPT) is addressed in this work. The synthesis of the subarray layout and of the subarrays weights is carried out to maximize the power transmission efficiency, while guaranteeing the full aperture coverage with simple domino-shaped tiles. Two design methodologies, one enumerative and one optimization-based, customized to the synthesis of small and larger apertures are presented. The best tiled array configuration is obtained through the maximization of the beam collection efficiency (BCE) for a given collection area where the receiving rectenna system is assumed. A set of representative numerical examples, including both ideal and real antenna models, is shown to prove the effectiveness of the proposed architectural solution as well as of the clustering methods. Analyses considering different array dimensions and sizes of the collection area, when scanning the beam off-boresight also along diagonal directions, are given to assess the performance of the proposed solutions.